2016
DOI: 10.4081/jbr.2016.5667
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3,5-diiodo-L-thyronine on the liver of high fat diet fed rats

Abstract: Experimental studies have highlighted that the administration of 3,5-diiodo-L-thyronine (T2) to rats fed diets rich in lipids induces a decrease of cholesterol and triglycerides plasma levels and body weight (BW) without inducing liver steatosis. On the basis of these observations we carried out some experimental in vivo studies to assess the effects of multiple high doses of T2 on the pituitary thyroid axis of rats fed diet rich in lipids. Fifteen male Wistar rats were divided into three groups of five animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…As discussed below, indeed, 3,5-T2 has some T3-like effects [182][183][184][185][186][187] in the absence of thyrotoxic side effects, at least when used at low concentrations [20,188]. On the contrary, at higher concentrations, it has been reported to suppress TSH and the HPT axis [189][190][191] and even to cause adverse cardiac effects similar to those observed in hyperthyroidism [190].…”
Section: The 35-diodothyronine (35-t2) As a Hormonementioning
confidence: 95%
See 4 more Smart Citations
“…As discussed below, indeed, 3,5-T2 has some T3-like effects [182][183][184][185][186][187] in the absence of thyrotoxic side effects, at least when used at low concentrations [20,188]. On the contrary, at higher concentrations, it has been reported to suppress TSH and the HPT axis [189][190][191] and even to cause adverse cardiac effects similar to those observed in hyperthyroidism [190].…”
Section: The 35-diodothyronine (35-t2) As a Hormonementioning
confidence: 95%
“…As discussed above, the treatment with 3,5-T2 may prevent the damage caused by HFD and reduce the circulating levels of LDL and TAG, as well as hepatic steatosis in overweight patients. It has been reported that the hormone may also reduce a pre-existing accumulation of fat in the rat liver [191]. In humans, a few studies have confirmed that the administration of 3,5-T2 can increase the resting metabolic rate, also reducing adiposity and body weight without side effects [250].…”
Section: The Ins and Outs Of 35-t2 Researchmentioning
confidence: 97%
See 3 more Smart Citations